2001
DOI: 10.1016/s0370-2693(01)00396-3
|View full text |Cite
|
Sign up to set email alerts
|

Noncompact Gepner models with discrete spectra

Abstract: We investigate a noncompact Gepner model, which is composed of a number of SL(2, R)/U(1) Kazama-Suzuki models and N = 2 minimal models. The SL(2, R)/U(1) Kazama-Suzuki model contains the discrete series among the SL(2, R) unitary representations as well as the continuous series. We claim that the discrete series contain the vanishing cohomology and the vanishing cycles of the associated noncompact Calabi-Yau manifold. We calculate the Elliptic genus and the open string Witten indices. In the A N −1 ALE models,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For the parent SL(2, R) conformal field theory, the construction was done in [51,52,53,55,56,57], with applications to AdS 3 string theory [58,59,60,61]. For the coset theory a similar construction should be possible [54,55], and should yield information on D-branes in NS5-brane backgrounds (see e.g. [62,63]).…”
Section: Discussionmentioning
confidence: 99%
“…For the parent SL(2, R) conformal field theory, the construction was done in [51,52,53,55,56,57], with applications to AdS 3 string theory [58,59,60,61]. For the coset theory a similar construction should be possible [54,55], and should yield information on D-branes in NS5-brane backgrounds (see e.g. [62,63]).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the Gepner model includes the so (8) We apply the same procedure to the models of [9,12] in the next section.…”
Section: Compact Gepner Modelsmentioning
confidence: 99%
“…In the noncompact theory, besides the continuous part of the spectrum which we treat in previous subsections, there is the discrete part of the spectrum. In this subsection, we consider the discrete part of the spectrum of ALE models [12].…”
Section: The Discrete Part Of the Ale Compactificationsmentioning
confidence: 99%
See 2 more Smart Citations